Family history a portrait of the Yulo family. - Tan, Ed Oliver Yulo
This study narrates how events in local history affect the fate and fortune of the Yulo family fromthe 1870s to the present. The information about the Yulo family was gathered from interview of key informants, archival research and from secondary sources. The study documents the history of the Yulo family which spans six generations from the time of Don Teodoro Yulo and its origins in Molo to its transfer to Negros Occidental. And that the demise of the sinamay industry in Panay and the emergence of the sugar industry at Negros are the principal facors that affected the family's fate and fortunes. These two factors were responsible in shaping the history of the Yulo family. From its rise into prominence to its involvement in local and reginal politics. And to decrease in the family's political and economic influence brought about by the growing complexity of the family and society. Lastly, the paper concludes that events in local society set the fate and fortune of the Yulo family.